2022
DOI: 10.3390/agronomy12102436
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity Analysis among Capsicum annuum Mutants Based on Morpho-Physiological and Yield Traits

Abstract: It is crucial to assess genetically superior parents when developing novel hybrids. This experiment was conducted to find out the diversity of 27 Capsicum annuum mutant lines derived from two varieties.To achieve the objective, 23 morpho-physiological and yield traits were recorded through two planting seasons. Highly significant differences (p0.01) were recorded among the studied traits. There was a strong to moderately positive phenotypic association between yield and all other morphological traits except fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Mardi et al (2022) also reported that transgressive segregants were the genotypes with a higher mean value than check genotypes, and the level of diversity was lower or equal to pure lines. Several studies have also carried out transgressive segregation estimations, including on wheat (Al-Bakry, 2021), mung bean (Jambormias et al, 2015;Maulida et al, 2022), sorghum (Munarti et al, 2022), and chili (Karim et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Mardi et al (2022) also reported that transgressive segregants were the genotypes with a higher mean value than check genotypes, and the level of diversity was lower or equal to pure lines. Several studies have also carried out transgressive segregation estimations, including on wheat (Al-Bakry, 2021), mung bean (Jambormias et al, 2015;Maulida et al, 2022), sorghum (Munarti et al, 2022), and chili (Karim et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The PCA results in the present study showed majority of the variability was explained by the first four principal components, which was similar to the reports of Sarmah, Sarma & Gogoi (2018) for different chili varieties of Assam. In a recent study on C. annum , it was observed that the percentage contribution by the first two principal component was 28% and 19% respectively ( Karim et al, 2022 ). In this respect, the current study showed high percentage contribution from the first two components, together accounting for 51.39%.…”
Section: Discussionmentioning
confidence: 99%
“…It may be due to the lack of superior varieties available in the public domain or the use of low-quality capsaicin content lines for cultivation. To overcome this, information on morphological characteristics, evaluation of a large number of germplasm, diversity study and creation of gene bank is pre-requisite, allowing the exploration of genetic variability efficiently ( Santos-Pessoa et al, 2018 ; Karim et al, 2022 ). Heritability criteria determine the extent to which it is transmissible from parents to offspring and is mostly preferred when used in association with other parameters ( Afiah, Mohammad & Saleem, 2000 ; Munda, Dutta & Lal, 2021 ; Begum et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the evaluated genotypes, genotype 2 recorded the highest fruit yield per plant whereas genotype 13 recorded the highest green fruit weight (Table 1). Overall, these findings recommended that prior evaluation of mutant parental lines is very helpful for breeders to select the best performing parents for successful execution of their future breeding programmes [11].…”
Section: Fruit Yield Of Chillimentioning
confidence: 98%